Giant Intraductal Papilloma of Breast - Vidallé, Dalila; Lucena, María Eugenia; Sarancone, Sandra; Alonso, Encarnación; Crocco, Cristina; Pairola, Gabriela (British Journal of Healthcare and Medical Research, 2024)
Intraductal papillomas are the most common form of papillary lesions. Despite their benign histological aspect, intraductal papillomas may appear with malignant growths, and a biopsy-based diagnosis involves the risk of underestimating breast cancer. This paper includes a literature review of the most relevant studies published to date in relation to a case of giant intraductal papilloma. Treatment is not consistent and depends on the result of clinical and pathological correlations. Therefore, gynecologists need to distinguish women who may be enrolled in the surveillance program from women requiring additional surgical therapy.